Estudo das condições de cultivo e adaptação do inóculo de Pichia stipitis ATCC 58376 para a produção de etanol a partir do hidrolisado hemicelulósico de farelo de girassol. - Tavares, Bruna (2013)
There are currently several studies aiming to convert plant biomass, which offers low cost and high generation in a sustainable and alternative energy source, thus adding economic value to the material. Lignocellulosic fibers, after passing through specific pretreatment of hydrolysis, originate fermentable sugars that can be biotransformed on second-generation ethanol. The breaking of this complex results in two main fractions, the cellulosic and the hemicellulosic fractions. The cellulosic one is still a challenge due to the cost, since it requires a pretreatment with high concentrations of acids and high thermal energy, and an enzymatic treatment too. The hemicellulosic fraction is more easily removable and it is composed primarily of xylose, but this sugar is not easily fermentable by traditional yeasts. The Pichia stipitis yeast has been studied due to its ability to use pentoses, appearing to be promising yeast for further industrial application. For this reason, this work aimed to evaluate fermentation parameters such as pH, temperature and agitation for ethanol production by Pichia stipitis ATCC 58376 in a medium consisting of the hemicellulosic hydrolyzate of sunflower meal, a by-product of sunflower oil extraction. In addition, the effects of inoculum adaptation were evaluated through the cultivation of cells in the hydrolyzed one and the reuse of the cells recovered at the end of the fermentation process. Sunflower meal was subjected to acid hydrolysis with sulfuric acid 6% (m/v), 120 atm in 20 min, resulting in a hemicellulosic hydrolyzate with 8.06 g.l-1 of glucose, 49.93 g.L-1 of xylose, 8.67 g.L-1 of arabinose, 3.55 g.L-1 of acetic acid, 0.031 g.L-1 of hydroxymethylfurfural, 0.033 g.L-1 of furfural, and 0.89 g.L-1 of phenols. The hydrolyzed one was detoxified by pH changes and adsorption with activated carbon to reduce or eliminate compounds formed during the hydrolysis, which are toxic to microbial metabolism. After this treatment, there was a reduction of 58% of acetic acid, and furfural, hydroxymethylfurfural and phenols were not detected in the hydrolyzate. Fermentations were conducted according to a factorial 33- DCCR, with 8 major tests, 6 axial and 3 central, totalizing 17 tests in different conditions of pH, temperature and agitation. Data analysis was performed using the STATISTICA 8.0 program. The tests showed no significant difference between them until the period of 72 hours, since in the test 14 (pH 5.0, 30ºC and 234 rpm) and in the 15, 16 and 17 central points (pH 5.0, 30° C and 150 rpm) it was verified the largest concentrations of ethanol, 13.31 g.L-1 and 13.28 g.L-1 respectively after 84 hours, regardless of the condition of the inoculum preparation. Efficiency and productivity were the same for the last five tests (13, 14, 15, 16 and 17): 0.45 g. g-1 and 0.185 g.l-1 .h-1after 84 hours of fermentation. The optimization of the process led to a final production of ethanol of 13.92 g.l-1, 4.38% higher than test 13, yield equivalent to the theoretical, 0, 51g.g-1, and productivity of 0.165 g.L-1.h-1 after 84 hours of fermentation.